A Benchmarking Survey of Open Access Funds at the University of California - Swift, Allegra; Taylor, Anneliese (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2025)
Objective – The purpose of this study was to examine the status and viability of application-based open access funds (OAFs) across the University of California (UC) Libraries to assist with long-term planning for this type of funding at UC.Methods – In 2022, the authors surveyed the 10 UC campus libraries about both the outcome of an earlier UC-wide OAF pilot and the current status of application-based OAFs to support article processing charges (APCs), book processing charges (BPCs), and open educational resources (OERs). Five campuses reported having a current OAF. These five campuses responded to additional questions about their budgets and their sustainability, the number of publications funded, policies, and staffing resources for managing the OAF.Results – Five UC campuses had an active application-based OAF, with budgets or expenditures ranging from $20,000 - $271,000 annually. Only two campuses felt their budget was sustainable. One of the five campuses closed its fund after the survey. The number of staff resources per fund ranged from 1 to 6 with 3 to 32 hours of work weekly. Funding policies were similar to other institutional OAFs with some distinctions. All campuses had revised their criteria to disallow funding for journals covered by UC’s transformative open access agreements.Conclusion – Providing application-based funds for OA publishing at high-publishing academic institutions requires a substantial budget and workforce. Though these funds benefit some authors, the wider equity of APCs and BPCs needs to be considered.